The efficacy of essential amino acid supplementation for augmenting dietary protein intake in older adults: implications for skeletal muscle mass, strength and function. Issue 2 (14th May 2021) - Ispoglou, Theocharis; Witard, Oliver C.; Duckworth, Lauren C.; Lees, Matthew J.
Abstract : The primary aim of this review is to evaluate the efficacy of essential amino acid (EAA) supplementation as a strategy to increase dietary protein intake and improve muscle mass, strength and function in older adults. A sufficient daily protein intake is widely recognised to be fundamental for the successful management of sarcopenia in older undernourished adults. In practice, optimising protein intakes in older adults is complex, requiring consideration of the dose and amino acid composition (i.e. a complete EAA profile and abundant leucine content) of ingested protein on a per meal basis, alongside the age-related decline in appetite and the satiating properties of protein. Recent studies in older adults demonstrate that EAA-based supplements are non-satiating and can be administered alongside food to enhance the anabolic properties of a meal containing a suboptimal dose of protein; an effect magnified when combined with resistance exercise training. These findings support the notion that EAA supplementation could serve as an effective strategy to improve musculoskeletal health in older adults suffering from non-communicable diseases such as sarcopenia. Compliance is critical for the long-term success of complex interventions. Hence, aspects of palatability and desire to eat are important considerations regarding EAA supplementation. In conclusion, EAA-based supplements enriched with l -leucine offer an alternative strategy to whole protein sources to assist older adults in meeting protein recommendations. In practice, EAA supplements could be administered alongside meals of suboptimal protein content, or alternatively between meals on occasions when older adults achieve their per meal protein intake recommendations.